1988
DOI: 10.1017/s0021932000017557
|View full text |Cite
|
Sign up to set email alerts
|

A survey of family planning in the Philippines

Abstract: Summary. In a multi-centre survey in 1986, 400 married Filipino women aged 15-40 were interviewed about their use of contraceptive methods, and specifically about their perceptions of the effects on health of oral contraceptives and their attitudes to contraceptive methods. The sample was randomly selected in the urban and rural areas surveyed and cannot be considered representative for the country as a whole. The results showed that women hold definitive views on the health risks posed by oral contraceptives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Partnership between the church and health care centers in advocating consistent information concerning birth spacing and limiting pregnancies would avoid confusing messages to the rural Filipino community. Riphagen et al's (1988) study revealed the existence of definitive views of Filipino couples concerning health risks associated with using modern contraceptive methods such as birth control pills and vasectomy. This study has similarly found that Filipino couples perceive modern contraceptives to have irreversible side effects and prefer to use traditional methods of contraception such as the withdrawal and rhythm methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partnership between the church and health care centers in advocating consistent information concerning birth spacing and limiting pregnancies would avoid confusing messages to the rural Filipino community. Riphagen et al's (1988) study revealed the existence of definitive views of Filipino couples concerning health risks associated with using modern contraceptive methods such as birth control pills and vasectomy. This study has similarly found that Filipino couples perceive modern contraceptives to have irreversible side effects and prefer to use traditional methods of contraception such as the withdrawal and rhythm methods.…”
Section: Discussionmentioning
confidence: 99%
“…Rather modern contraceptive methods such as birth control pills were introduced strictly as a means to decrease the number of children by preventing pregnancy. However, definitive severe side effects, deformed babies, and other health risks for oral contraceptive methods contributed to low prevalence use of contraceptives (Riphagen, de la Cueva, & Koelb, 1988).…”
mentioning
confidence: 99%